Patient-reported outcomes in ZUMA-7, a phase 3 study of axicabtagene ciloleucel in second-line large B-cell lymphoma - Elsawy, Mahmoud; Chavez, Julio C.; Avivi, Irit; Larouche, Jean-François; Wannesson, Luciano; Cwynarski, Kate; Osman, Keren; Davison, Kelly; Rudzki, Jakob D.; Dahiya, Saurabh; Dorritie, Kathleen; Jaglowski, Samantha; et al. (Blood, 2022)
Here, we report the first comparative analysis of patient-reported outcomes (PROs) with chimeric antigen receptor T-cell therapy vs standard-of-care (SOC) therapy in second-line relapsed/refractory large B-cell lymphoma (R/R LBCL) from the pivotal randomized phase 3 ZUMA-7 study of axicabtagene ciloleucel (axi-cel) vs SOC. PRO instruments were administered at baseline, day 50, day 100, day 150, month 9, and every 3 months from randomization until 24 months or an event-free survival event. The quality of life (QoL) analysis set comprised patients with a baseline and ≥1 follow-up PRO completion. Prespecified hypotheses for Quality of Life Questionnaire-Core 30 (QLQ-C30) physical functioning, global health status/QoL, and EQ-5D-5L visual analog scale (VAS) were tested using mixed-effects models with repeated measures. Clinically meaningful changes were defined as 10 points for QLQ-C30 and 7 for EQ-5D-5L VAS. Among 359 patients, 296 (165 axi-cel, 131 SOC) met inclusion criteria for QoL analysis. At day 100, statistically significant and clinically meaningful differences in mean change of scores from baseline were observed favoring axi-cel over SOC for QLQ-C30 global health status/QoL (estimated difference 18.1 [95% confidence interval (CI), 12.3-23.9]), physical functioning (13.1 [95% CI, 8.0-18.2]), and EQ-5D-5L VAS (13.7 [95% CI, 8.5-18.8]; P < .0001 for all). At day 150, scores significantly favored axi-cel vs SOC for global health status/QoL (9.8 [95% CI, 2.6-17.0]; P = .0124) and EQ-5D-5L VAS (11.3 [95% CI, 5.4-17.1]; P = .0004). Axi-cel showed clinically meaningful improvements in QoL over SOC. Superior clinical outcomes and favorable patient experience with axi-cel should help inform treatment choices in second-line R/R LBCL. This trial was registered at www.clinicaltrials.gov as #NCT03391466.